"Caring for the Mine": Women in Capitalist Accumulation in the Peruvian Andes. (16th September 2020) - Pérez, Leda M; De la Puente, Lorena
Abstract: A "service provision" value chain that sustains the activities of the Las Bambas copper mine cuts across rural communities and the mining town, connected by the invisibilized work of indigenous and/or migrant women, through their maintenance of the rural homestead, or in their provision of feminized services, essential to men who work in the urban center near the mine. We argue that in this case women's access to mining's benefits and/or jobs in both rural and urban spaces is mediated by gender, as mining's direct and indirect effects serve to consolidate their social reproductive roles.